Strategy Implementation Practices and Growth of Deposit Taking Savings and Credit Cooperatives in Embu County, Kenya - Celina Wangari, Mourine; Waithaka, Dr. Paul (Journal of Strategic Management, 2023)
Purpose: This study involved determination of how the aspects organization structure and organization culture affect the growth of SACCOs and specifically those that take deposits in the County of Embu. Methodology: The theories that guided this study included the institutional theory and Edgar Schein theory. Descriptive survey research design was adopted targeting 11 savings and credit cooperatives in Embu County as the unit of analysis and 77 respondents formed the unit of observation where census was used. The validity as well as the reliability of the questionnaires used in this study to collect primary data was determined through a pilot test with the overall Cronbach alpha coefficient value as 0.873. The project overseer who is a subject guru in the area of study went through the content of the research tool to determine if the tool used adequately captured the aspects being studied and thus ascertained for content validity. Relevant authorities including a letter of introduction from Kenyatta University which were used to explain the purpose of study and a permit for the research was sought before data collection in the field. The analysis was done through statistical package for social sciences version 24 utilizing means, standard deviations and regression analysis and presented through tables and figures. Findings: The findings were that organization culture had the greatest implication on SACCO growth followed by organization structure. It was concluded that strategy implementation practices have significant effect on growth of deposit taking savings and credit cooperatives in Embu County, Kenya. Recommendations: It was recommended senior management of the SACCOs in Embu should eliminate bureaucracies through minimization of the degree of formalization. The top management team in liaison with the boards of directors in SACCOs operating in Embu should review the existing values so as to bind employees together as they work to implement the formulated strategies.